2015
DOI: 10.1074/jbc.m114.630533
|View full text |Cite
|
Sign up to set email alerts
|

The N Terminus of Pro-endothelial Monocyte-activating Polypeptide II (EMAP II) Regulates Its Binding with the C Terminus, Arginyl-tRNA Synthetase, and Neurofilament Light Protein

Abstract: Background: Functional domains of pro-EMAP II play an important role in multi-aminoacyl tRNA synthetase (MSC) complexes. Results:The N terminus of Pro-EMAP II binds to its C terminus, arginyl-tRNA synthetase, and the neurofilament light subunit and contains a putative leucine zipper. Conclusion:The N terminus of pro-EMAP II facilitates its interaction with MSC complexes. Significance: Understanding these binding domains may provide important insights into transcriptional regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…2D), although previous studies found that the first 70 a.a. of AIMP1 is sufficient to maintain robust RARS binding (16). These findings suggest that rather the entirety of AIMP1 with an intact intra-molecular N- to C-terminus bond (9) was required for efficient AIMP3 binding. We hypothesize that the interaction site for AIMP3 is formed due to this intramolecular interaction within AIMP1.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…2D), although previous studies found that the first 70 a.a. of AIMP1 is sufficient to maintain robust RARS binding (16). These findings suggest that rather the entirety of AIMP1 with an intact intra-molecular N- to C-terminus bond (9) was required for efficient AIMP3 binding. We hypothesize that the interaction site for AIMP3 is formed due to this intramolecular interaction within AIMP1.…”
Section: Resultsmentioning
confidence: 96%
“…Instead of a GST-L domain found in Arc1p, the AIMP1 N-terminus contains a coiled-coil motif. All previously reported interactions for AIMP1 were mapped to this coiled-coil region (9). In addition, we previously reported intra-molecular bond within the AIMP1 protein (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, AIMP1 was a negative regulator of NF phosphorylation, and its overexpression or depletion could change the phosphorylation level of NFs, leading to the NF network disassembly. Recently, Xu et al discovered that the N terminus of AIMP1 was responsible for the binding to its C terminus and arginyl-tRNA synthetase (RARS), and it also colocalized to the NF-L subunit protein 41 . These findings suggest that AIMP1 plays an important role in NF assembly and axon maintenance, which provides a new idea for exploring the pathogenesis of neurological diseases.…”
Section: Biological Functions Of Aimpsmentioning
confidence: 99%